Constructing Palladium‐Based Crystalline@Amorphous Core–Shell Heterojunctions for Efficient Formic Acid Oxidation - Huiling Li; Jingkun Yu; Yongming Sui; Weibin Wang; Jiewen Liu; LiBo Sheng; Ankang Chen; Siyu Lu; Bo Zou (Advanced Science, 2025)
Abstract Constructing crystalline@amorphous heterostructures allows nanomaterials to maintain high electrical conductivity of crystalline structures while acquiring abundant active sites from amorphous structure. This emerging strategy has attracted considerable attention in electrochemical and photoelectrochemistry applications. However, achieving crystalline@amorphous heterostructures based on palladium (Pd) remains challenging due to the difficulties in balancing the transformation between these two phases. Here, a feasible strategy is developed to manufacture Pd‐based crystalline@amorphous core–shell structures through non‐metallic element doping. The obtained core–shell structures exhibit outstanding catalytic performance for formic acid oxidation (FAO) with mass activity of up to 2.503 A mg−1Pd. Detailed theoretical and experimental analyses reveal that the construction of crystalline@amorphous core–shell structures increase surface active sites, lowers the oxidation energy barrier, and enhances the selectivity of the direct pathway, thereby effectively facilitating the FAO process. This work demonstrates the feasibility of constructing efficient FAO catalysts using crystalline@amorphous core–shell structures and provides a new platform for achieving platinum‐group metals (PGMs) based crystalline‐amorphous heterostructures.